The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14238/pi58.3.2018.110-15
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between immunization status and pediatric diphtheria patients outcomes in the Sampang District, 2011-2015

Abstract: Background The number of diphtheria cases recently increased, such that an outbreak was declared in East Java Province, which includes the Sampang District. Immunization completion status is a determining factor for diptheria infection. Objective To investigate for correlations between immunization status and outcomes (severity level, fatality, and complications) of diphtheria patients in the Sampang District. Methods This analytic, cross-sectional study used secondary data from the East Java Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
1
0
3
Order By: Relevance
“…5,8 In this study, diphtheria occurred mostly in early childhood years (9 years and below) due to inadequate immune system performance. School-age children have increased frequency of contact with the disease-causing pathogen.. 9 In our study, male predominance was found in 20 cases (58.8%), a similar result to a study conducted at Gujarat in 2013 which also found male predominance (63%). 4 In this study, all cases were presented with pseudomembrane that were found most in pharynx (23 cases, 67.6%) and tonsil (21 cases, 61.8%).…”
Section: Resultssupporting
confidence: 89%
“…5,8 In this study, diphtheria occurred mostly in early childhood years (9 years and below) due to inadequate immune system performance. School-age children have increased frequency of contact with the disease-causing pathogen.. 9 In our study, male predominance was found in 20 cases (58.8%), a similar result to a study conducted at Gujarat in 2013 which also found male predominance (63%). 4 In this study, all cases were presented with pseudomembrane that were found most in pharynx (23 cases, 67.6%) and tonsil (21 cases, 61.8%).…”
Section: Resultssupporting
confidence: 89%
“…The results of this study complement the findings of Dhinata et al . 19 , which found no correlation between patient immunization status and severity, or fatality of diphtheria in the Sampang District of Indonesia.…”
Section: Discussionmentioning
confidence: 94%
“…6 Berdasarkan penelitian sebelumnya, komplikasi difteri terjadi pada 26 dari 71 penderita difteri atau 36,6%. 7 Komplikasi penyakit difteri pada pasien dengan bull neck, gangguan pada jantung, saluran pernapasan, ginjal, ataupun saraf berisiko menyebabkan kematian. 8 Di Indonesia, terdapat 24 kasus pasien difteri meninggal pada tahun 2016 (CFR difteri 5,8%), 13 kejadian di antaranya ada di Jawa Barat (CFR difteri 9,78%).…”
unclassified
“…Namun, pada penelitian tersebut ditemukan bahwa pasien difteri dengan status imunisasi lengkap mengalami difteri yang ringan dan tingkat fatalitas lebih rendah dibandingkan pasien dengan status imunisasi tidak lengkap atau tidak imunisasi, walaupun hasil tersebut tidak bermakna secara statistik. 7 Penelitian ini memiliki asosiasi dengan penelitian pada pasien difteri dewasa oleh Pantukosit dkk 16 di Buri Ram, Thailand. Pantukosit dkk melaporkan bahwa imunisasi tidak lengkap akan meningkatkan risiko komplikasi pada pasien difteri, insiden komplikasi merupakan indikator dalam penggolongan difteri berat.…”
unclassified